154 Transient left ventricular systolic dysfunction during intravenous immunoglobulins treatment for myasthenia gravis exacerbation. (8th December 2021) - Boiago, Mauro; Dellino, Carlo Maria; Marra, Martina Perazzolo; Babuin, Luciano; Famoso, Giulia; Fraccaro, Chiara; Napodano, Massimo; Tarantini, Giuseppe; Cacciavillani, Luisa; Iliceto, Sabino
Abstract: A 61-year-old man suffering from myasthenia gravis with predominant bulbar involvement since 10 months before admission, was diagnosed with thymoma in April 2021. He had no relevant comorbidities except for history of polymorphic ventricular ectopic beats. In this regard, in 2019 he had undergone transthoracic echocardiogram and coronary computed tomography angiography, which resulted both normal. After 1 month, due to poor response to standard medical therapy with prednisone and pyridostigmine and in preparation for thymectomy, an intravenous immunoglobulins (IVIG) treatment was prescribed leading to mild clinical improvement (Myasthenia Gravis Foundation of America Clinical Classification IIIA—MGFA). Two weeks later, the patient underwent robotic-assisted thoracoscopic thymectomy without complications. Pathological findings were consistent with type B1 Thymoma classified as Masaoka Stage IIB (TNM Stage pT1a). After discharge the patient complained a rapid worsening of neurological symptoms (MGFA IIIB) leading to an urgent hospitalization for Myasthenia Gravis exacerbation in the middle of June. On admission Intravenous Immunoglobulins (IVIG) treatment was immediately started. After administration of the second IVIG dose, he had a myasthenic crisis complicated by refractory heart failure with significant increase of cardiac troponin up to 5.768 ng/L, requiring invasive ventilation, inotropic support and urgent transfer to the Cardiac Intensive Care Unit (CICU). The 2D echo showed severe left ventricular systolic dysfunction (LVEF 20%) with diffuse hypokinesis. The patient underwent cardiac catheterization and coronary angiography that confirmed severe reduction of the LVEF (LVEF 23%) with embolic occlusion of the distal posterior descending coronary artery (PDA) without other significant coronary artery stenosis. An endomyocardial biopsy was performed, which revealed cardiomyocytes of normal dimensions with sporadic cytoplasmic vacuolization and excluded signs of inflammation, fibrosis, necrosis and viral myocarditis. The day after the patient completed IVIG treatment. During the following days, despite persistence of severe left ventricular systolic dysfunction, he was successfully weaned form inotropic and ventilatory support. At neurological evaluation he reported persistence of severe bulbar involvement with upper and lower limbs weakness. Five days later, the patient had a sudden cardiac arrest for pulseless electrical activity. Advanced cardiac life support requiring inotropes and invasive ventilation was performed for 28 min before returning to spontaneous circulation. The echocardiogram excluded pulmonary embolism and mechanical complications but showed severe left ventricular systolic dysfunction. A new coronary angiography showed clear coronary arteries including PDA. Because of severe haemodynamic compromise, an Impella CP device was implanted and set at maximum support level (P8 flow, >3 L/min). A neurological exam revealed no severe neurological sequelae. As a result of the long CPR the patient had a massive left haemothorax, initially treated with multiple blood transfusions and pleural drainage. Two days later, due to persistence of haemodynamic instability and active pleural bleeding with incessant severe anaemia the case underwent a Heart Team discussion where it was decided to escalate Impella CP device to Veno-Arterial Extracorporeal Membrane Oxygenation (VA-ECMO) and then perform a video-assisted thoracoscopic evacuation of the haemothorax. Both procedures were carried out without complications. The patient had an immediate haemodynamic improvement which led to rapid weaning from inotropic support. Haemoglobin was stable. The 2D echo showed significant improvement of the LVEF (40%). After 3 days, given the persistence of haemodynamic stability, ECMO device was removed and invasive ventilation stopped shortly afterwards. Eleven days later, another 2D echo demonstrated complete recovery of left ventricular systolic function (LVEF 59%). Notwithstanding, the patient reported a progressive worsening of neurological symptoms with generalized myasthenia and severe bulbar involvement (MGFA IVB) along with episodes of respiratory muscle fatigue requiring non-invasive ventilation. For this reason, the patient was transferred to Subintensive Respiratory Unit and the case underwent a new multidisciplinary discussion involving neurologists, cardiologists and haematologists. Specialists agreed upon potential causal role of IVIG treatment in transient left ventricular dysfunction and considered re-administration absolutely contraindicated. Thus, they prescribed five plasmapheresis treatments and up-titration of corticosteroid therapy (methylprednisolone up to 60 mg od). An immediate and outstanding improvement of neurological symptoms was obtained (MGFA IIIA) and the patient was discharged from hospital 1 week later.